1996
DOI: 10.1128/jvi.70.8.5170-5176.1996
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine A-resistant human immunodeficiency virus type 1 mutants demonstrate that Gag encodes the functional target of cyclophilin A

Abstract: The cellular peptidyl-prolyl isomerase cyclophilin A is incorporated into human immunodeficiency virus type 1 virions via contacts with the proline-rich domain of the Gag polyprotein. Cyclosporine A and nonimmunosuppressive analogs bind with high affinity to cyclophilin A, compete with Gag for binding to cyclophilin A, and prevent incorporation of cyclophilin A into virions; in parallel with the disruption of cyclophilin A incorporation into virions, there is a linear reduction in the initiation of reverse tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(51 citation statements)
references
References 39 publications
0
50
1
Order By: Relevance
“…We did not detect the previously described mutation A92E or G94D (1,12) in the sequences of the CypA binding loop from naturally resistant virus isolates. Mutants carrying these mutations had been selected from strain NL4-3 when it infected CD4 ϩ HeLa cells and was passaged in the presence of NIM811.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…We did not detect the previously described mutation A92E or G94D (1,12) in the sequences of the CypA binding loop from naturally resistant virus isolates. Mutants carrying these mutations had been selected from strain NL4-3 when it infected CD4 ϩ HeLa cells and was passaged in the presence of NIM811.…”
Section: Discussioncontrasting
confidence: 75%
“…So far, all CypA variants with reduced catalytic activities have a concomitant reduction in substrate affinity (26); thus, the isomerase activity cannot be separated from the binding function. The binding of CypA to the HIV-1 CA protein as well as PPIase activity are known to be inhibited by Cs (12,48) and the nonimmunosuppressive cyclosporine NIM811 (10,87).…”
Section: Discussionmentioning
confidence: 99%
“…A92T has not been previously reported, but a charge-adding mutation at this residue, A92E, is known to arise when HIV-1 is passaged in HeLa cells in the presence of CsA, thus conferring CsA resistance and in some cell lines actually conferring CsA dependence on the virus (1,12); this phenomenon was later shown to reflect high levels of CypA in HeLa cells (70). Our experiments make it clear that CypA is present at substantial levels in the Mus- telidae cell lines that we used ( Fig.…”
Section: )mentioning
confidence: 99%
“…3). Disruption of CypA incorporation c 2008 The Societies and Blackwell Publishing Asia Pty Ltd into the virion by CsA administration or by Gag mutations resulted in reduction in infectivity of the produced viruses (85,89,91,(95)(96)(97)(98). Several reports have shown that both CA dimerization and CypA multimerization are required for the efficient CA-CypA binding which is critical for HIV-1 infectivity (99,100).…”
Section: Cyclophilin A: a Host Factor Involved In Retroviral Replicationmentioning
confidence: 99%